2019
DOI: 10.1007/s13197-019-03714-9
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and microbiological characteristics of honey obtained through sugar feeding of bees

Abstract: This study was planned to characterize the physicochemical and antioxidant properties, and microbiological quality of honey obtained from the sandbar pumpkin field. In this study, four sugar supplemented and one control (without sugar fed) honey sample was used. Results revealed that all samples exhibited appropriate maturity considering their low moisture content (* 19%) and high total solids (* 80%) and TSS (* 79%). Total acidity (\ 40 meq/kg) and pH (* 4.5) directed the absenteeism of detrimental fermentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
4
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 31 publications
5
22
4
6
Order By: Relevance
“…Honey's microbiological quality indicates the hygienic conditions of its handling, processing and storage. The bacterial and fungal contamination in honey is an indication of non-hygienic conditions during collection, processing, manipulation, handling and storage (Tchoumboue et al 2007).Bacterial load associated with the hive bees honey in the present investigation was comparatively higher than documented by Kamal et al (2019), where total viable count of microorganisms in analysed honey samples varied from 1.44 to 1.52 log CFU/g. Likewise, Babarinde et al (2011) reported that the total viable count of microorganisms in the analysed honey samples varied from 2.9 to 3.1 log CFU/g.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Honey's microbiological quality indicates the hygienic conditions of its handling, processing and storage. The bacterial and fungal contamination in honey is an indication of non-hygienic conditions during collection, processing, manipulation, handling and storage (Tchoumboue et al 2007).Bacterial load associated with the hive bees honey in the present investigation was comparatively higher than documented by Kamal et al (2019), where total viable count of microorganisms in analysed honey samples varied from 1.44 to 1.52 log CFU/g. Likewise, Babarinde et al (2011) reported that the total viable count of microorganisms in the analysed honey samples varied from 2.9 to 3.1 log CFU/g.…”
Section: Discussioncontrasting
confidence: 45%
“…Conversely, the figure reported (< 10 5 CFU/g) for bacterial count in the current study might be due to the bee keeping practices applied during harvesting of honey. Also, the environmental conditions of the selected locations might contribute to the microbial contamination (Kamal et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Diastase activity of honey ranged from 6.02° to 21.99° Göthe [ 176 ]. Kamal et al [ 177 ] reported values of diastase activity ranging from 12.63° to 16.33° Göthe for five honey samples harvested from Bangladesh. Khalafi et al [ 178 ] reported values of diastase activity between 5.8° and 21.3° Göthe for ten types of honey.…”
Section: Resultsmentioning
confidence: 99%
“…18 Therefore, early harvest of the immature honey leads to high moisture content. 19 High water content increases the possibility of honey being fermented during long storage periods. 20 The average water content of our MH samples (18.31 ± 1.52 g per 100 g) were below the required threshold standard of the European Regulations of Quality (no more than 20 g per 100 g).…”
Section: Discussionmentioning
confidence: 99%